Method for removing arsenic from smoke containing arsenic and solidifying arsenic - LIU ZHIYONG; YAO WEI; LI SIWEI; ZHOU YAMING; JIANG TAO; LI QIHOU; LIU ZHIHONG; LI YUHU (2017)
The invention relates to a method for removing arsenic from smoke containing arsenic and solidifying arsenic. The method comprises the following steps that production of comprehensive recovering of valuable metal such as arsenic, antimony, lead and bismuth from smelting smoke containing arsenic, antimony and lead is conducted, and arsenic accumulation in a system is reduced to enable arsenic to be harmless. According to the method provided by the invention, through normal-pressure alkaline leaching, soluble arsenic in the smoke is removed, after trivalent arsenic in a leaching agent is changed to pentavalent arsenic through catalytic oxidation, a stable solid arsenic mineral is compounded through a lime arsenic precipitation method, and then the solid arsenic mineral is solidified through a cement solidifying mode; and leaching slag is subjected to the processes such as washing, reduction smelting and oxidizing blowing, and then all valuable elements are recycled to the maximum. According to the method, by re